2018
DOI: 10.1177/2047487318778349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trends in cardiovascular risk factors between two regions with and without a community and primary care prevention programme

Abstract: Background The effect of primary prevention of cardiovascular disease is debated. The Västerbotten Intervention Programme (VIP) is an individual and community-based public health programme that comprises the whole county of Västerbotten (VB). In the neighbouring county of Norrbotten (NB), no programmes have been implemented. Method Between 1994 and 2014, five surveys were performed in the two counties on persons aged 40 to 75 years within the Northern Sweden MONICA Study. The number of subjects participating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
2
23
3
Order By: Relevance
“…We found no significant differences in health-related QoL between the population of VB, with the health intervention program, and NB, without any similar program. The only previous research where VB is compared to another county, also based on the 2014 MONICA population survey and using similar methods as in this report, reported a faster decline in blood pressure and smoking in Västerbotten but similar trends for diabetes, cholesterol and obesity (8). However, the results are different from a previous evaluation of the impact of the program on self-reported health, in which a significant and positive effect was reported (7).…”
Section: Discussion Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…We found no significant differences in health-related QoL between the population of VB, with the health intervention program, and NB, without any similar program. The only previous research where VB is compared to another county, also based on the 2014 MONICA population survey and using similar methods as in this report, reported a faster decline in blood pressure and smoking in Västerbotten but similar trends for diabetes, cholesterol and obesity (8). However, the results are different from a previous evaluation of the impact of the program on self-reported health, in which a significant and positive effect was reported (7).…”
Section: Discussion Resultscontrasting
confidence: 76%
“…Still, several studies have evaluated the effects of the Västerbotten program on intermediate outcomes and report improvement on lifestyle parameters such as reducing smoking (5), increasing physical activity (6) and that self-reported health has improved (7), in particular in those with initial poor and fair health. A study of time trends in cardiovascular risk factors in VB, using the MONICA Study, showed a faster improvement in blood pressure and smoking but no difference in the prevalence of diabetes, cholesterol levels or BMI compared to the neighbouring county of NB (8).…”
Section: Introductionmentioning
confidence: 99%
“…We found no significant differences in health-related QoL between the populations of VB (which had been subjected to the VIP) and NB (which had not). The only other research that compares VB with NB, that also uses the 2014 MONICA Study data, and that employs similar methods to those in this report, found a faster decline in blood pressure and smoking in VB when the two counties in question were compared, but found similar trends when the two were compared with respect to diabetes, cholesterol and obesity (8). However, the results of our study differ from a previous evaluation of the VIP's impact on self-reported health, which found the intervention had had a significant and positive effect in VB (7).…”
Section: Discussionsupporting
confidence: 62%
“…These studies report that certain lifestyle parameters have been enhanced by, among other things, a reduction in smoking (5), an increase in physical activity (6) and an improvement in self-reported health particularly among those whose initial state of health was poor or fair (7). In addition, a study of trends over time in respect of cardiovascular risk factors in VB, using the World Health Organization's Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA) Study, showed a faster improvement in blood pressure and smoking but no difference in the prevalence of diabetes, cholesterol levels or BMI compared to the neighbouring county of NB (8).…”
mentioning
confidence: 99%
“…Editor's presentation: 'You say you love your children above all else, and yet you are stealing their future in front of their very eyes' Massimo F Piepoli 1,2 Intergenerational associations of ideal health behaviours…”
mentioning
confidence: 99%